2021
DOI: 10.3390/ani11020462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artemisia absinthium and Malva sylvestris on Antioxidant Parameters and Abomasal Histopathology in Lambs Experimentally Infected with Haemonchus contortus

Abstract: This study evaluated the effect of Artemisia absinthium and Malva sylvestris on antioxidant response and histopathological changes in the abomasa of the Haemonchus contortus infected lambs. Twenty-four lambs were divided into four groups: unsupplemented lambs (UNS), lambs supplemented with A. absinthium (ART), lambs supplemented with M. sylvestris (MAL), and lambs supplemented with both plants (ARTMAL). Lambs were infected orally with approximately 5000 third-stage (L3) larvae of H. contortus. The experiment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
2
7
1
Order By: Relevance
“…Two volatile compounds, 2-methyl-1-pentanethiol and trimethyl-heptadien-4-one, were identified at higher concentrations in this isolate. The activity of these compounds as a repellent, odor character, insecticides, and nematicides have already been reported earlier by Huang et al (2018) and Mravčáková et al (2021). Similarly, the compounds, dodecadienal, undecane, and nerolic acid observed throughout metabolite profiles in the present study have already been reported as nematicidal, antibacterial, and antifungal compounds (Caboni et al, 2012;White et al, 2019;Sarsaiya et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Two volatile compounds, 2-methyl-1-pentanethiol and trimethyl-heptadien-4-one, were identified at higher concentrations in this isolate. The activity of these compounds as a repellent, odor character, insecticides, and nematicides have already been reported earlier by Huang et al (2018) and Mravčáková et al (2021). Similarly, the compounds, dodecadienal, undecane, and nerolic acid observed throughout metabolite profiles in the present study have already been reported as nematicidal, antibacterial, and antifungal compounds (Caboni et al, 2012;White et al, 2019;Sarsaiya et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…The number of eosinophils in abomasal tissue in our study was higher in both treated groups than in the Control group at the end of the experiment, but the number was highest in the group supplemented with Se. The number of tissue eosinophils in our previous study did not differ significantly between the control and animals treated with medicinal plants ( Mravčáková et al., 2021 ). We, therefore, concluded that determining the changes in eosinophil numbers at necropsy was inappropriate and that supplementation with medicinal plants did not affect eosinophil levels in the tissues.…”
Section: Discussionmentioning
confidence: 58%
“…Dilatation and damage to glands, lymphoid aggregates, and oedema were more notable in the Herbmix group than the Control and Selplex groups, probably due to the stronger inflammation in this group. Our previous study also found that inflammation was strongest in the abomasa of lambs infected with H. contortus and supplemented with a mixture of A. absinthium and M. sylvestris compared to the unsupplemented control ( Mravčáková et al., 2021 ). The prolonged and more severe inflammation in the group supplemented with medicinal plants may have been due to the delayed and incomplete defence against parasites, where a large number of parasites can cause lesions of the abomasal mucosa, which can lead to stronger local inflammation ( Toscano et al., 2019 ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…superoxide radicals, hydroxyl radicals, and hydrogen peroxide) [ 10 ]. Feed supplementation with medicinal herbs containing bioactive compounds may attenuate the adverse effects of parasite infection by stimulating endogenous antioxidant defense systems and helping trigger local immune responses in the abomasal mucosa of small ruminants [ 11 , 12 ]. Polyphenols are the most common antioxidants known for their immunomodulatory and anti-inflammatory activities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%